RETRACTED: AUDIT PROCUREMENT AS A TOOL TO IMPROVE THE EFFICIENCY OF SPENDING BUDGET FUNDS IN THE CONTRACT SYSTEM - A. Gladchuck (Гуманитарные и юридические исследования)
RETRACTED ARTICLEThe process of spending the country's budget is inextricably linked to the implementation of financial controls on their effective and targeted use. To a considerable degree of financial control affect the implementation of the budget holders of purchasing procedures to ensure its activities and the performance of its functions. Through the contract system in the field of procurement is spending most of the budget of the state. The legislation on the contract system in accordance with part 1 of article 2 of the Law № 44-FZ is based on the provisions of the Budget code of the Russian Federation and during the procurement procedures of goods, works and services customers use budget funds in order to implement quality and comprehensive financial control, in the audit in the field of procurement control and accounting bodies of the Russian Federation cover issues on the effective use of budget funds by customers in procurement. This scientific article reveals the content, problems and direction of development of audit in the field of procurement, mechanisms of efficiency audit conducted by the control and accounting bodies of the Russian Federation as a necessary condition for the implementation of external financial control of procurement in order to improve the efficiency of budget spending in the contract system. At the same time, the article classifies the types of the most common violations of the legislation on the contract system in the field of procurement and the practice of control bodies to identify and prevent them in the future, and also proposes measures to improve the results of procurement procedures in terms of quality, effectiveness and achievement of the necessary tasks defined by Law No. 44-FZ, including the improvement of activities carried out in the framework of procurement audit. As part of the implementation of procurement audit activities, it is necessary to focus the issues of audit activities mainly on the identification of facts that link the identified violation with the inefficient spending of budgetary funds and the failure to achieve the results of procurement determined by the legislation on the contract system and the budget legislation of the Russian Federation. Taking into account the above, as well as the relationship between budget relations and the implementation of audit in the field of procurement by control and accounting bodies of the Russian Federation in order to comply with budget legislation and other regulatory legal acts regulating legal relations on the preparation, execution and expenditure of budget funds of the country in the field of procurement, the relevance of the topic discussed in this article is confirmed.